Reference frameworks for the health management of measles, breast cancer and diabetes (type II) - Brand, Helmut; Schröder, Peter; Davies, John K; Escamilla, Ixhel; Hall, Caroline; Hickey, Kieran; Jelastopulu, Eleni; Mechtler, Reli; Yared, Wendy Tse; Volf, Jaroslav; Weihrauch, Birgit (Central European journal of public health, 2006)
This paper presents reference frameworks which order effective and feasible policies and interventions for the health management of measles, breast cancer and diabetes (type II). These reference frameworks can be used to rapidly appraise regional health policy documents and existing health management systems. Furthermore, the reference frameworks can serve health policy makers for the planning of health management measures.
Keywords: nádory prsu; Diabetes Mellitus, Type 2; Female; Health Policy; spalničky; management nemoci; Measles; Breast Neoplasms; Humans; ženské pohlaví; lidé; diabetes mellitus 2. typu; Europe; zdravotní politika; benchmarking; Evropa; Disease Management; Benchmarking